Transformasi Tradisi Ekonomi Islam: Perspektif Sosiologi dan Antropologi pada Pasar Modal Syariah di Indonesia - Tri Cahyani , Putri; Abdal, Abdal; Rizaludin, Rizaludin; Cahyani, Putri Tri; Arifin, Tajul (ASAS, 2025)
The development of the Islamic capital market in Indonesia reflects the transformation of Islamic economic practices in response to social, cultural, and modern economic system dynamics. This transformation is not merely related to normative compliance with Sharia principles but also involves social and cultural processes that shape how Muslim communities interpret and engage with contemporary economic activities. This study aims to analyze the transformation of Islamic economic practices within the Indonesian Islamic capital market from sociological and anthropological perspectives. The research employs a qualitative method using a literature review approach, involving an analysis of Islamic economics literature, economic sociology, economic anthropology, as well as regulations and practices governing the Islamic capital market. The findings indicate that the Islamic capital market in Indonesia has evolved as a social institution that internalizes Islamic ethical values within modern market mechanisms, particularly through regulatory frameworks, Sharia-compliant stock screening mechanisms, and financial instrument innovation. From a sociological perspective, the Islamic capital market contributes to the formation of new social norms and social legitimacy in the investment activities of Muslim communities. Meanwhile, from an anthropological perspective, this transformation reflects processes of cultural adaptation and the construction of contextual Islamic economic symbols without detaching from religious identity. This study concludes that the Islamic capital market in Indonesia represents an adaptive and multidimensional transformation of Islamic economics, affirming the continued relevance of Islamic values within modern economic systems.